Relationship Between Asthma Control as Measured by the Asthma Impairment and Risk Questionnaire (AIRQ) and Patient Perception of Disease Status, Health-Related Quality of Life, and Treatment Adherence - Reibman J; Chipps BE; Zeiger RS; Beuther DA; Wise RA; McCann W; Gilbert I; Eudicone JM; Gandhi HN; Harding G; Cutts K; Coyne KS; et al. (Journal of Asthma and Allergy, 2023)
Joan Reibman,1 Bradley E Chipps,2 Robert S Zeiger,3 David A Beuther,4 Robert A Wise,5 William McCann,6 Ileen Gilbert,7 James M Eudicone,7 Hitesh N Gandhi,7 Gale Harding,8 Katelyn Cutts,8 Karin S Coyne,8 Kevin R Murphy,9 Maureen George10 1New York University School of Medicine, New York, NY, USA; 2Capital Allergy & Respiratory Disease Center, Sacramento, CA, USA; 3Department of Clinical Science Kaiser Permanente Bernard J. Tyson School of Medicine, Pasadena, CA, USA; 4National Jewish Health, Denver, CO, USA; 5Division of Pulmonary and Critical Care Medicine, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 6Allergy Partners, Asheville, NC, USA; 7BioPharmaceuticals Medical, AstraZeneca, Wilmington, DE, USA; 8Evidera, Bethesda, MD, USA; 9Boys Town National Research Hospital, Boys Town, NE, USA; 10Office of Research & Scholarship, Columbia University School of Nursing, New York, NY, USACorrespondence: Joan Reibman, New York University School of Medicine, 550 1st Avenue, Room NB7N24, New York, NY, 10016, USA, Tel +1 212-263-6479, Fax +1 212-263-8442, Email joan.reibman@nyumc.orgPurpose: Critical asthma outcomes highlighted in clinical guidelines include asthma-related quality of life, asthma exacerbations, and asthma control. An easy-to-implement measure of asthma control that assesses both symptom impairment and exacerbation risk and reflects the impact of asthma on patients’ lives is lacking. Hence, the objective of this study was to assess the Asthma Impairment and Risk Questionnaire (AIRQ®) construct validity relative to patient self-perception of asthma status and validated disease-specific patient-reported outcome (PRO) measures.Patients and methods: Baseline data were analyzed from patients (aged ≥ 12 years) with asthma participating in a 12-month observational study assessing the ability of AIRQ to predict exacerbations. At entry, patients completed a sociodemographic questionnaire, AIRQ, 3 questions addressing self-perceived asthma status, Saint George’s Respiratory Questionnaire (SGRQ), mini-Asthma Quality of Life Questionnaire (AQLQ), and Adult Asthma Adherence Questionnaire (AAAQ). Descriptive statistics were calculated for demographic and clinical characteristics. AIRQ construct validity was evaluated by assessing correlations between total AIRQ score and patient self-assessments, SGRQ, mini-AQLQ, and AAAQ scores. Comparisons of SGRQ, mini-AQLQ, and AAAQ total and component/domain scores by AIRQ control category were performed using general linear models and Scheffe’s post hoc adjustments for pairwise comparisons.Results: A total of 1112 patients were enrolled: 70% female, 78% White, mean (standard deviation) age 43.9 (19.5) years. There were highly significant correlations between AIRQ score and patient self-perception of overall control (r = 0.69; p < 0.001), total SGRQ (r = 0.74, p < 0.001), and mini-AQLQ (r = − 0.78, p < 0.001) scores. As AIRQ control category worsened, so did total and domain SGRQ, mini-AQLQ, and AAAQ impediment-to-inhaled-corticosteroid-adherence scores (all pairwise comparisons p < 0.001).Conclusion: Findings demonstrate the construct validity of AIRQ relative to patient self-perception of asthma status, disease-specific PRO measures, and treatment adherence barriers. AIRQ can be a useful instrument to raise awareness of the unrecognized impacts of asthma on patients’ lives.Keywords: exacerbation, patient-reported outcomes, construct validity, impact of asthma